Hubungan Psikopatologi dengan Mekanisme Koping pada Perempuan dengan HIV/AIDS di RSCM Tahun 2016 - Yunita Tambunan; Petrin Redayani; Kristiana Siste; Natalia Widiasih (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction : Women with HIV/AIDS have greater risk than men in having psychopathology although the data about this is still scarce. To resolve stress, patients with HIV/AIDS build many coping mechanism, often the maladaptive ones. This study aims to assess the relationship between psychopathology and coping mechanism in women with HIV/AIDS. Method : A cross-sectional study was conducted to determine psychopathology (using SCL-90 questionnaire), and coping mechanism (using Brief COPE questionnaire) among women with HIV/AIDS at Pokdisus of Cipto Mangunkusumo Hospital. Results : Among 116 subjects, 37,1% had psychopathology with depression as the most common psychopatology (44.2%). Most respondents used religion as their coping mechanism (46,6%). The coefficient correlation between psychopathology and mechanism of coping was r=0,292 and p=0,001. Conclusion : There was a significant difference with positive correlation between psychopathology and mechanism of coping. Respondents without psychopathology usually used religion coping mechanism whereas respondents with psychopathology often used religion and self blame coping. A comprehensive management in female with HIV/AIDS can be done by early detection of their psychopathology and coping mechanism.